Day-of-the-Week Effect and Investors’ Psychological Mood Testing in a Highly Mispriced Capital Market - Rizky Luxianto; Usman Arief; Muhammad Budi Prasetyo (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Research Aims: This research examines investors’ psychological moods which cause day-of-the-week anomalies in highly mispriced stock markets. Design/methodology/approach: We use a sample from the Indonesian capital market as, in the Asian region, this country is considered to have a highly mispriced capital market. We decompose the stock price index in Indonesia into speculative, less speculative, and non-speculative indexes. We employ the mean and variance regressions to control the heteroscedasticity and serial correlation. Novelties: Our novelties are two fold. We postulate a method to decompose stock price indexes in Indonesia (the JKSE, LQ 45, and Kompas 100) into speculative, less speculative, and non-speculative indexes. Secondly, we estimate the mean and variance levels simultaneously to get a robust estimation result of the anomaly. Research Findings: We empirically find that the behavior mood hypothesis is supported only during normal periods, when investors tend to be irrational and use their good mood to trade on speculative stocks on a Wednesday and sell them on Monday. In other periods, rationality and psychological effects play a role with Indonesian investors, when their mood is good they are more active in trading less speculative stocks, to avoid higher risks and earn higher returns from those less speculative and non-speculative stocks.